Validity and practicality of Ecology Project Based Practicum Worksheets to Improve Science Process Skills - Ekariana S. Pandia; Ayu Wahyuni; Nursamsu Nursamsu; Nurhasnah Manurung (Postgraduate, University of Mataram, 2023)
The research objective was to determine the validity of the due diligence worksheet based on an ecological project to improve science process skills. To find out the practicality of ecological project-based practicum worksheets to improve science process skills. The study method developed using Research and Development (R&D) consists of several stages of research implementation, namely the first stage is preparing for the Experiment/Preliminary Design. The second stage of product creation (process), includes: assessing students' abilities in selecting and using materials, tools and techniques. Next, the third stage of product assessment (appraisal), includes: assessing the products produced by students according to the established criteria. The target research subjects were 30 FKIP UNSAM Biology Education students. Data collection techniques carried out included using tests, observation sheets, questionnaires, interviews, assessment of Practicum Worksheets, portfolios, field notes and assessment rubrics. The results of this research show that the product feasibility validation test with an average score of 88.22% is declared very valid, while the practicalization test with an average score of 84.2% is declared very valid. So it can be concluded that the Practical Worksheet product is suitable for use for Biology practical learning activities